Reply to the 'Comment on "Energy harvesting from shadow-effect"' by A. K. Das, V. K. Sahu, R. S. Ajimshaa and P. Misra, Energy Environ. Sci., 2021, 10.1039/D0EE03214J. Issue 7 (16th June 2021) - Nandakumar, Dilip Krishna; Ravi, Sai Kishore; Suresh, Lakshmi; Tan, Swee Ching
Abstract : We discuss the comment of Das et al. on our recent paper. Abstract : In their comment, Amit et al. propose an alternative working mechanism for the origin of photocurrent and photovoltage in our shadow-effect energy generators (SEG). However, in this reply we have elucidated the fundamental difference in the connection pattern of our measurements against Amit et al.' s. This misunderstanding has led them to propose an alternate working mechanism for our device. The working mechanism proposed by the authors does seem appropriate and gives a better performance when both the metallic thin film and the underlying Si are a part of the electrical circuit, whereas our proposed mechanism of the work function shift in the semiconductor-metal system seems appropriate for the connection pattern that we had adopted for our measurements.